PROPOSED CONSIDERA TIONSFOR REVISION OF EBCS-8: 1995FOR CONSERVATIVE SEISMIC ZONING AND STRINGENT REQUIREMENTS FOR TORSIONALLY IRREGULAR BUILDINGS - Kinde, Samuel (Zede Journal of Ethiopian Engineers and Architects, 2023)
There is a significant variation in seismic zoning adopted in Ethiopia for urban areas between the seismic building code [1]' and those reported in other research publications. F.urther, it is also believed that the torsional loads recommended by the current seismic building code to account for accidental torsion are not conservative,.enough for a seismically active country such as Ethiopia where th,re is inadequate quality control in construction practices. This paper deals with proposals for implementing a conservative seismic zoning for urban areas such as Addis Ababa and implementing a more stringent torsional load requirements in the current Ethiopian seismic building code [2J.